2021
DOI: 10.1590/s1980-657420210020520
|View full text |Cite
|
Sign up to set email alerts
|

Performance, metabolic, hemodynamic, and perceived exertion in the six-minute step test at different heights in a healthy population of different age groups

Abstract: This study aimed to compare the performance, metabolic, hemodynamic, and perceived exertion during the 6-minute step test (6MST) conducted with different step heights in healthy subjects and also to compare the performance between different age groups for each step height. The association between age, body mass index, level of physical activity, and lower limb measurements with performance were also evaluated. Methods: This is a cross-sectional study. Anthropometric measures, physical performance, and cardiova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
1
1
1
Order By: Relevance
“…In our study, participants who finished the 6MST without interruption climbed an average of 92.3 steps, and those who suspended or required interruption climbed, on average, 37.7 and 76.4, respectively. The participants performed the 6MST on a 20cm-high step and climbed an average of 77.6 steps, which demonstrates a lower performance when compared to the study by Oliveira et al 15 , performed with healthy individuals with the same type of step, climbed an average of 173.8 steps.…”
Section: Discussioncontrasting
confidence: 63%
“…In our study, participants who finished the 6MST without interruption climbed an average of 92.3 steps, and those who suspended or required interruption climbed, on average, 37.7 and 76.4, respectively. The participants performed the 6MST on a 20cm-high step and climbed an average of 77.6 steps, which demonstrates a lower performance when compared to the study by Oliveira et al 15 , performed with healthy individuals with the same type of step, climbed an average of 173.8 steps.…”
Section: Discussioncontrasting
confidence: 63%
“…Evidenciou-se uma queda não significativa da SpO 2 (p=0,009) no sexto minuto. 15 , realizado com indivíduos saudáveis, com a mesma altura de degrau, que subiram uma média de 173,8 degraus.…”
Section: Análise Estatísticaunclassified
“…The ACSM stated that 6MST requires more energy than 6MWT and has a higher oxygen demand due to different body movements (9) . A study by Oliveira et al showed that a higher step height induced greater cardiovascular stress without exceeding the submaximal levels of the test, indicating that the 6MST can be used as an accurate tool to assess aerobic capacity in healthy individuals (13) . Albuquerque VS et al predicted normative reference values and a reference equation for the 6-minute step test in the Brazilian population, which is not applicable in the present region due to anthropometric variability, and validated it only in the Brazilian region (18) .…”
Section: Introductionmentioning
confidence: 99%